USING MODIFICATION OF VOWELS IN CONNECTED SPEECH ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the phenomenon of vowel modification in connected speech, detailing how vowels can change their pronunciation in fluent communication compared to careful speech. It identifies several types of vowel modification, including vowel reduction, lengthening, diphthongization, and coarticulation, explaining how these changes are influenced by factors such as speech rate, stress patterns, dialectal variation, and phonetic context. The article discusses the effects of vowel modification on intelligibility and naturalness in spoken language, emphasizing its significance for language learners and speech practitioners. By highlighting the importance of understanding vowel modifications, the article aims to enhance awareness of fluent communication practices and improve listening comprehension and speaking fluency in language acquisition.